Funding Analysis, Company Cash Flow Statement and Its Effect on Banking Firm Value - Siti Kustinah (GoAcademica Research & Publishing, 2020)
This study aimed to analyze the effect of funding and cash flow statements on firm value. This research uses quantitative research with an associative approach. The type of data used is primary data and secondary data. This research was conducted on ten expert accountants using questionnaires and Likert scale calculations. Data were collected by questionnaire method and literature study. The source of the data used in this study comes from the BBCA's financial statements for the 2017-2020 period, which have been audited and obtained from IDX and the results of questionnaires to expert respondents—testing the data using validity test, reliability test, and hypothesis testing. The research findings indicate that Funding and Cash Flow Statements have a direct, positive, and significant effect on firm value.